Effect Of Yogic Practices On Spiritual Intelligence Of Prospective Teachers - Sharma, Sunil; Samita (International Research Journal of Ayurveda & Yoga, 2024)
Background: Spiritual intelligence (SI) refers to the ability to access higher meanings, values, and purposes in life, influencing personal development and professional effectiveness. In the context of education, SI is vital for prospective teachers, as it enhances emotional regulation, self-awareness, and a deep connection to teaching practices. Previous studies suggest that yogic practices can contribute to the development of SI by promoting self-reflection, mindfulness, and emotional balance. This study investigates the impact of a structured yoga intervention on the spiritual intelligence of prospective teachers. Aim: The primary aim of this study is to assess the effect of an eight-week structured yoga intervention on the spiritual intelligence of prospective teachers at the Government College of Education, Chandigarh. Materials & Methods: A total of 60 prospective teachers were randomly assigned to either the experimental (n = 30) or control (n = 30) group. The experimental group participated in an eight-week yoga intervention, while the control group received no intervention. Spiritual intelligence was measured using the Spiritual Intelligence Scale developed by Dr. Dhar S. and Dr. Dhar U. (2010) at two points: before (pre-test) and after (post-test) the intervention. Discussion and Conclusion: The study concludes that Yogic practices significantly enhance spiritual intelligence among prospective teachers. These findings support the integration of Yoga into teacher education programs to foster personal growth and improve emotional and spiritual development. Future research could explore the long term effects of such interventions and their impact on teaching efficacy and student outcomes.